Modelo de maturidade para a indústria 4.0 para PME’s brasileiras: um estudo de caso em uma indústria de ração animal - Oliveira Júnior, Libório de (2018)
The frequent changes in the economic, social, environmental and technological scenarios impose on industries the creation of physical and virtual structures that allow close cooperation and rapid adaptation throughout the entire life cycle of their products, from innovation and development to production and distribution. This work presents a maturity model, constructed from a systematic review of the literature, to evaluate the level of maturity in industries of developing countries in relation to their insertion in the environment of Industry 4.0. Was used the maturity model development methodology that is based on six phases: Scope, Design, Fill, Test, Implement and Maintain. At the end of the process is a model divided into seven dimensions, grouped into three aspects: Technology, Organization and People, which was applied in a medium-sized industry producing animal feed. The practical application of the model found that the level of maturity of this company is not yet within the practices of Industry 4.0, but is in the process of scanning since the information is replaced by connected components and systems. It is concluded that the company, which is at a level 2 of 5, needs to equalize all related aspects, starting with the insertion of the theme "Industry 4.0" in the planning guidelines, investment in IoT technologies in every line of production and training employees.